The "nature" of Common Core: Connecting science and literature through the natural world. (2nd January 2016) - Britton, Stacey; McCullough, Amber; Ortwein, Mark; Parker, Mary Ann
ABSTRACT: The unit described in this article targets lower elementary students, encouraging them make connections between literature, nature, personal explorations, and the Earth. Students were encouraged to keep a daily journal from our outdoor nature visits, drawing pictures of what they see, and recording activities from class that improved their understanding of the content being introduced. While multiple content areas could be integrated through this lesson, we focused this unit on one guiding question: Why does the Sun appear to move throughout the day? Additionally, the classroom teacher was encouraged to integrate activities and to make learning interdisciplinary. (Connections are provided throughout this unit and in the Appendix.) We found that the repetition of ideas was very helpful for the students to actually begin making sense of what rotation meant in their life and was provided through the center activities. We also found that students were naturally curious and expressed great interest in discussing the changes they observed, and they were able to make connections with the constant change of seasons they experience in the Northern Hemisphere.